Knowing Enough and Space-Making for Microbes in Sake Fermentation Practices - Maya Hey (Engaging Science, Technology, and Society, 2025)
This paper examines how one comes to know microbes in fermentation settings. Based on praxiographic data from field research at a sake brewery in Japan, the paper analyzes how brewers work in an anticipatory manner to make spaces that encourage certain microbes to thrive throughout the recurring steps of fermentation—an approach one might call space-making. While the hegemony of western science prioritizes technoscientific ways of knowing precisely which microbes are active and why, western science is not the only epistemic framework for encountering microbial life, and so this paper takes seriously the provocation of what it means to practice a form of knowing enough through which one can know microbes otherwise. After elaborating on different fermenting spaces, its tools, and its cleaning practices, the paper discusses the tension that arises between the temporalities of microbial metabolisms and temporalities of laboratory/scientific equipment. The paper concludes with thoughts on a form of knowing microbes that is based on inquiry and interdependence, evading modernist schemas of control.